2023
DOI: 10.2147/jep.s379805
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antimicrobial Activity Evaluation of Selected Medicinal Plants in Ethiopia

Abstract: Background The emergence and spread of resistant microbes continue to be a major public health concern. Effective treatment alternatives, particularly from traditionally used medicinal plants, are needed. Objective The main objective of this study was to conduct phytochemical screening and antimicrobial activity evaluation of selected traditionally used medicinal plants in Ethiopia. Methods The ethnomedicinal use value frequency index (FI) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…There have been several previous studies on the topics discussed, including ( Zega et al, 2021), (Megawati, 2020), (Ernilasari et al, 2021), (Widowati et al, 2021), and (Dubale et al, 2023). Broadly speaking, previous research contains similarities and differences with this research.…”
Section: Literature Reviewmentioning
confidence: 65%
“…There have been several previous studies on the topics discussed, including ( Zega et al, 2021), (Megawati, 2020), (Ernilasari et al, 2021), (Widowati et al, 2021), and (Dubale et al, 2023). Broadly speaking, previous research contains similarities and differences with this research.…”
Section: Literature Reviewmentioning
confidence: 65%
“…Tannins function as reducing agents, courtesy of phenolic groups capable of releasing electrons. In the context of Ag + bioreduction, tannins play a role in contributing electrons, leading to the deposition of the generated Ag particles [13,33] …”
Section: Resultsmentioning
confidence: 99%
“…In the context of Ag + bioreduction, tannins play a role in contributing electrons, leading to the deposition of the generated Ag particles. [13,33] The FTIR spectrum of ethanolic extract C. alata leaf and biosynthesized AgNPs (Figure 1) was studied to detect functional groups present in plant ethanolic extract and subjected to reduction of Ag + ions and capping for AgNPs. The broad and shallow absorption at 3400 cm À 1 region in the ethanolic extract C. alata leaf spectra indicates the presence of the hydroxyl (OH) group from polyphenolic compounds such as flavonoids.…”
Section: Green Synthesis Of Agnps Using Ketepeng Leaf Extractmentioning
confidence: 99%
“…There is a shift of focus to medicinal plants due to the increased antimicrobial resistance, severe adverse effects, high costs of synthetically available drugs and the community perception towards modern health care practice [33]. Many studies demonstrated that plant extracts are highly effective against bacterial microorganisms due to enormous kind of secondary metabolites [33,34,35].…”
Section: Discussionmentioning
confidence: 99%